2021
DOI: 10.4236/abc.2021.113010
|View full text |Cite
|
Sign up to set email alerts
|

Association between Uric Acid and Metabolic Syndrome in Homozygous Sickle Cell Patients

Abstract: The objective of this study was to assess the association between uric acid and the metabolic syndrome and its components in homozygous sickle cell patients. This is a prospective case/control study of sickle cell SS patients. Each patient was matched to a control of the same sex and age ± 2 years. In our framework, we used the criteria for defining metabolic syndrome according to International Diabetes Federation (IDF) 2009. Assay of all biological parameters was performed with the ARCHITECT ci4100, Abbot (Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In SCD, the mechanism often suggested is overproduction from an increased marrow activity and turnover of nucleic acids secondary to hemolysis. Several studies have reported elevated uric acid levels in SCD patients: 26.9%, 20 30%, 21 28%, 22 9.2%. 23 Compared to these studies, the higher prevalence of hyperuricemia observed in this study could be explained, on the one hand, by the hemolytic phenomena related to the endemicity of infectious and parasitic diseases in our environment.…”
Section: Sample Collection and Laboratory Analysismentioning
confidence: 99%
“…In SCD, the mechanism often suggested is overproduction from an increased marrow activity and turnover of nucleic acids secondary to hemolysis. Several studies have reported elevated uric acid levels in SCD patients: 26.9%, 20 30%, 21 28%, 22 9.2%. 23 Compared to these studies, the higher prevalence of hyperuricemia observed in this study could be explained, on the one hand, by the hemolytic phenomena related to the endemicity of infectious and parasitic diseases in our environment.…”
Section: Sample Collection and Laboratory Analysismentioning
confidence: 99%